Record of an established population of Palaemon macrodactylus Rathbun, 1902 (Decapoda, Palaemonidae) in the Mediterranean Sea: confirming a prediction - CUESTA, J. A.; BETTOSO, N.; COMISSO, G.; FROGLIA, C.; MAZZA, G.; RINALDI, A.; RODRIGUEZ, A.; SCOVACRICCHI, T. (Mediterranean Marine Science, 2014)
The capture of larvae of Palaemon macrodactylus off Mallorca (Balearic Islands) has been recently reported as evidence of a potential presence of a population of this species in the Mediterranean Sea. Photos of this species, taken during dives in the Sacca di Goro (northern Adriatic) were published in the same year, but no specimen could be collected at that time. Herein we report the capture in 2013 of numerous individuals of the oriental shrimp, including ovigerous females, both in the Sacca di Goro and in the Lagoon of Marano and Grado (northern Adriatic Sea, Italy), confirming the existence of a well-established population of this species in the Mediterranean Sea.